Development of aortic endothelial cells to express CD37 and CD73 isolated from alpha 1,3-galactosyltransferase knock-out and MCP expressing pig - Jin-Gu No; Sung-June Byun; Hyeon Yang; Sun A Ock; Jae-Seok Woo; Hwi-Cheul Lee; In-sul Hwang; Ji-Youn Kim; Sang Hyoun Park; Joo Young Lee; Keon Bong Oh (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Acute vascular rejection has been known as a main barrier occurring in a xenograted tissue of alpha 1,3-galactosyltransferase knock-out (GalT KO) pig into a non-human primate (NHP). Adenosine which is a final metabolite following sequential hydrolysis of nucleotide by ecto-nucleotidases such as CD39 and CD73, act as a regulator of coagulation, and inflammation. Thus xenotransplantation of CD39 and CD73 expressing pig under the GalT KO background could lead to enhanced survival of recipient NHP. We constructed a human CD39 and CD73 expression cassette designed for endothelial cell-specific expression using porcine Icam2 promoter (pIcam2-hCD39/hCD73). We performed isolation of endothelial cells (pAEC) from aorta of 4 week-old GalT KO and membrane cofactor protein expressing pig (GalT-MCP/-MCP). We were able to verify that isolated cells were endothelial-like cells using immunofluorescence staining analysis with von Willebrand factor antibody, which is well known as an endothelial maker, and tubal formation assay. To find optimal condition for efficient transfection into pAEC, we performed transfection with GFP expression vector using four programs of nucleofection, M-003, U-023, W-023 and Y-022. We were able find that the program W-023 was optimal for pAEC with regard to viability and transfection efficiency by flow cytometry and fluorescent microscopy analyses. Finally, we were able to obtain GalT-MCP/-MCP/CD39/CD73 pAEC expressing CD39 and CD73 at levels of 33.3% and 26.8%, respectively. We suggested that pACE isolated from GalT-MCP/-MCP pig might be provided as a basic resource to understand biochemical and molecular mechanisms of the rejections and as an alternative donor cells to generate GalT-MCP/-MCP/CD39/CD73 pig expressing CD39 and CD73 at endothelial cells.